Overview of Trematodes (Trematoda) of mammals in Uzbekistan - Shakarboev, Erkinjon B.; Jumamuratov, Jasurbek E.; Khosilova, Guzal A. (Acta Biologica Sibirica, 2024)
Based on the research and the analysis of literary data, we identified 27 species of trematodes from 19 genera, 12 families and 7 orders, which parasitise mammals in Uzbekistan. The families Brachylaemiidae and Paramphistomatidae, with 6 and 5 species, respectively, showed the highest species diversity. These two families contained 40.7% of all recorded trematode species infecting mammals. The families Fasciolidae and Echinostomatidae include 3 species each, Dicrocoeliidae and Plagiorchidae – 2 species each, with 1 trematode species in each of the remaining 6 families.